2018
DOI: 10.1002/chem.201704618
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Nickel Pyridinedicarboxamidate Complexes to Explore the Properties of High‐valent Oxidants

Abstract: High-valent Ni oxidants have been implicated in hydrocarbon oxidation catalysis, however, little is understood about the properties of these oxidants. Herein, a family of Ni complexes supported by a pyridinedicarboxamidate ligand and different ancillary ligands was synthesized. The series spans coordination numbers 4, 5, and 6, and contains neutral, mono- and di-anionic donor types. X-ray crystallography and magnetic measurements showed that the 4-coordinate complexes were square planar and low spin (S=0) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 69 publications
(58 reference statements)
9
16
1
Order By: Relevance
“…This contrasts with the previously reported [Ni III (OAc)­(L*)] complex which was thermally stable at 25 °C when prepared with NaOCl/AcOH . The instability may be attributed to ligand oxidation (at the isopropyl group) which we previously observed for L, but not for L*. ,, …”
Section: Resultscontrasting
confidence: 92%
See 4 more Smart Citations
“…This contrasts with the previously reported [Ni III (OAc)­(L*)] complex which was thermally stable at 25 °C when prepared with NaOCl/AcOH . The instability may be attributed to ligand oxidation (at the isopropyl group) which we previously observed for L, but not for L*. ,, …”
Section: Resultscontrasting
confidence: 92%
“…The τ 4 parameters for 1a and 2a were 0.18 and 0.26, respectively, which indicated that the complexes were in slightly distorted square planar geometries (τ 4 = 0 for pure square planar, τ 4 = 1 for pure tetrahedral) . The geometric parameters of 1a and 2a were similar to those of previously reported [Ni II (OX)­(L*)] − (OX = OH, OCO 2 H, OAc, ONO 2 ) and [Cu II (OH)­(L)] − complexes. ,,,, …”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations